PENGARUH RETURN ON ASSETS (ROA) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERBANKAN (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2023 - Safitri, Zaini; Hulu, Paolinus; Johan, Muhammad (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2024)
ABSTRAC Credit growth disbursed by the banking industry in 2023 slowed down compared to 2022. In 2023, banking loans will grow by around 10.38% on an annual basis (YoY). The achievement of banking credit disbursement in 2023 was recorded to grow slower than in 2022 which was able to reach 11.35% YoY. Perry Warjiyo (2024) stated that